Growth Hormone Research Society perspective on the development of long-acting growth hormone preparations. Issue 6 (June 2016) - Christiansen, Jens Sandahl; Backeljauw, Philippe F; Bidlingmaier, Martin; Biller, Beverly M K; Boguszewski, Margaret C S; Casanueva, Felipe F; Chanson, Philippe; Chatelain, Pierre; Choong, Catherine S; Clemmons, David R; Cohen, Laurie E; Cohen, Pinchas; et al.
Abstract : Objective: The Growth Hormone (GH) Research Society (GRS) convened a workshop to address important issues regarding trial design, efficacy, and safety of long-acting growth hormone preparations (LAGH). Participants: A closed meeting of 55 international scientists with expertise in GH, including pediatric and adult endocrinologists, basic scientists, regulatory scientists, and participants from the pharmaceutical industry. Evidence: Current literature was reviewed for gaps in knowledge. Expert opinion was used to suggest studies required to address potential safety and efficacy issues. Consensus process: Following plenary presentations summarizing the literature, breakout groups discussed questions framed by the planning committee. Attendees reconvened after each breakout session to share group reports. A writing team compiled the breakout session reports into a draft document that was discussed and revised in an open forum on the concluding day. This was edited further and then circulated to attendees from academic institutions for review after the meeting. Participants from pharmaceutical companies did not participate in the planning, writing, or in the discussions and text revision on the final day of the workshop. Scientists from industry and regulatory agencies reviewed the manuscript to identify any factual errors. Conclusions: LAGH compounds may represent an advance over daily GH injections because of increased convenience and differing phamacodynamic properties, providing the potential for improved adherence and outcomes. Better methods to assess adherence must be developed and validated. Long-term surveillance registries that include assessment of efficacy, cost-benefit, disease burden, quality of life, and safety are essential for understanding the impact of sustained exposure to LAGH preparations.